Manajemen perpustakaan dalam mendukung gerakan literasi digital di Madrasah Aliyah Negeri 2 Kota Madiun - Eny Supriati (Jurnal Kajian Informasi dan Perpustakaan, 2021)
Information and technology developments have changed the culture of manual library services to digital. School libraries have a role in providing digital information to students in schools. This study aimed to determine library management in supporting the digital literacy movement in Madrasah Aliyah Negeri 2, Madiun City, through an analysis of library planning, implementation, and evaluation activities. The results showed that the library's digital literacy program planning activities were based on class, school culture, and the community. The process of formulating digital literacy program planning used an analysis of the madrasa work plan, previous programs, internal and external factors, analysis of the competence and potential of program implementers, and socialization. The library implementation activities are formulating programs, dividing the implementing team, and creating work instructions by establishing coordination and good relations with program implementers, the head of the library, the implementing team and teachers, the head of the library, and the head of the madrasa. Evaluation activities are in the form of internal evaluation by the head of the library and the head of the madrasa, performance evaluation by the implementing team, evaluation of performance results, and evaluation of program achievement. Madrasah Aliyah Negeri 2, Madiun City, has developed android-based library access, electronic catalog, and social media. Thus, it concludes that library management has been running quite well in supporting the digital literacy movement in Madrasah Aliyah Negeri 2 Madiun City.